Deskripsi Hasil Belajar Ditinjau Dari Kecenderungan Gaya Belajar Siswa pada Mata Pelajaran Kimia di MAN 2 Kota Palu - Annisaa Kusumaningrum; Sri Mulyani Sabang (Media Eksakta, 2021)
This study aimed to describe learning outcomes of students at MAN 2 Palu in terms of the tendency of learning styles in chemistry. This type of study was descriptive research. Sampling was carried out using the proportional stratified random sampling technique consisted of 93 students. Data collection technique used instruments of learning style questionnaire and learning outcomes test as well as daily test scores of Acid and Base Solutions. The results showed that students of Class XI MIA at MAN 2 Palu had various learning styles. There were 49 students (53%) with a tendency to visual learning styles, 31 students (34%) with an auditorial learning style, and 13 students (13%) with a kinesthetic learning style. Students with visual learning style performed an excellent category of learning outcomes of 25,81% compared to students with an auditorial learning style of 16% and with a kinesthetic learning style of 8,6%.